Modificação superficial do tecido 100% algodão tratado com plasma - Freitas, Duciane Oliveira de (2009)
The 100% cotton fabric (CO)* treated with plasma of methane CH4 has direct application in all areas that needs of aqueous solutions repellent material like coatings and uniforms applied biomedical, aeronautics, and automobile between others. 100% cotton fabric (CO) samples were treated by plasma with two differents atmosphere: Methane gas (CH4), treatment time was varied in 10 in 10 min. until 60 min., and mixture methane/argon (CH4/Ar), it was varied the proportion 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 e 9:1, with treatment time of 30 minutes. In both, the fluxe was 5 sccm (second cubic centimeter), pressure 6 mbar, voltage 490 V and current 0,15A. The objective of work was measure the superficial tension of 100% CO then it treated with plasma, using contact angle measures of water and glycerol with the surface. The samples were tested after treatment, with 8 and 12 months to verify the superficial modification effects. It was verified an increase of hydrophobility with the Sessile drop values varied between 116,69º to 137,85º and it carried on after 12 months. The no treated samples shows contact angle equal 0º. OES analysis and Raman spectroscopy were accomplished. In the SEM analysis was verified oligomers. The plasma treatment is correct environmental, It turning greater than conventional treatments